Oficina de brinquedos e brincadeiras na promoção de comportamentos sociais - Santos Soares, Leys Eduardo dos (Educación Física y Ciencia.)
This article presents the analysis of the results of an intervention with Toys and Games Workshop (OBBA by its acronym in Portuguese) on the behavior of children identified with antisocial conducts. Qualitative approach research, research-action type, was carried out with a group of the 5th year of elementary school, in a public school in João Pessoa-PB. The students were identified through an observation script and evaluated, before and during the workshop, by the Anti-Social Trend Scale (ETA by its acronym in Portuguese). After implementing the project over a period of time, in its different stages (Presentation, Evaluation, Implementation, and Intervention), a significant increase in social actions such as lending, offering, assisting, thanking, praising and dialoguing in those with antisocial behavior was evidenced.